"Mon Dieu", Bourdieu: The Magic of the Academy and Its Ancestor Cults - Hobbis, Geoffrey; Hobbis, Stephanie (Anthropologica, 2013)
By looking at the vast corpus of texts on Pierre Bourdieu in an unexpected way, this article uses a material culture analysis to study the social relations of academics. We find Bourdieu's name and his dictionary of concepts used not only as signifiers of his theory but also for its mana, the effi cacy of its social capital. Bourdieu is a ghost summoned by his inner circle that has turned his name and concepts into totems that are reinforced through ritualized writing, hence feeding the development and stewardship of Bourdieu's (and academia's) ancestor cult, its magic.